Korelasi Pengetahuan, Status Ekonomi, Paritas, dan Kepatuhan Konsumsi Tablet Fe dengan Kejadian Anemia pada Ibu Hamil di Wilayah Puskesmas Pedada Pesawaran Tahun 2025 - Nabela Dwi Damayanti; Nila Qurniasih; Yetty Dw Fara; Yunita Anggriani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Background Anemia in pregnant women has the potential to endanger both mother and child, the prevalence of anemia in Lampung Province increased to 9.10% in 2020. Causes of anemia include non-compliance during pregnancy with iron supplementation tablets, low knowledge, and other factors. The purpose of this study was to determine the correlation between knowledge, economic status, parity, and compliance with iron tablet consumption with the incidence of anemia. Method: This type of research is quantitative with a cross-sectional design. The study population was pregnant women with a sample of 68 respondents using a total sampling technique. The study was conducted in the Pedada Pesawaran Community Health Center working area from October 29, 2025, to December 2, 2025. Data collection used a questionnaire and the chi-square test. Results: Based on the results of the study, it was found that 35 (51.5%) had anemia, while 33 (48.5%) did not experience anemia. Knowledge was lacking in 31 (45.6%), knowledge was sufficient in 20 (29.4%), and knowledge was good in 17 (25%). Low economic status was low in 37 (54.4%), and high economic status was high in 31 (45.6%). Parity was at risk in 41 (60.3%), and parity was not at risk in 27 (39.7%). Further analysis showed a relationship between knowledge (p-value = 0.031), economic status (p-value = 0.001), parity (p-value = 0.015), and adherence to iron tablet consumption (p-value = 0.000) with the incidence of anemia in pregnant women. Therefore, it is recommended that pregnant women increase their adherence to regularly consuming iron tablets as a measure to prevent anemia from an early age.